High-performance B4C-LaB6 composite ceramics fabricated via hot-pressing sintering with La2O3 as sintering additive. Issue 23 (1st December 2021) - Yang, Mingsheng; Zhuang, Yanxin; Xing, Pengfei
Abstract: The B4 C-LaB6 composite ceramics were fabricated via hot-pressing sintering at 2050 °C and 20 MPa pressure with the mixture of boron carbide (B4 C) and 2–5 wt% lanthanum oxides (La2 O3 ) as raw materials. The effects of additive La2 O3 content on the microstructures and mechanical properties of composite ceramics were investigated, and reaction mechanisms of La2 O3 and B4 C at different temperatures were studied in detail. La2 CO5, La3 BO6 and LaBO3 were formed by the reactions of La2 O3 and B4 C at different temperatures, and finally LaB6 was formed below 1600 °C. The comprehensive mechanical properties of B4 C-LaB6 composite ceramics were optimized by adding 4 wt% La2 O3, the flexural strength, fracture toughness and Vickers hardness reached 350 MPa, 4.92 MP am 1/2 and 39.08 GPa, respectively. The high densification and flexural strength of composite ceramics achieved in the present study were attributed to LaB6 hindering the movement of grain boundary. However, the densification was reduced caused by CO as La2 O3 content increased to 5 wt%. The fast channel was formed via B4 C reacting with La2 O3, which accelerated migration of B4 C in the sintering process. The content of La2 O3 played an important role in the fracture mode of the composite ceramics, and ultimately affected the fracture toughness of the composite ceramics.